Waste-Free Use of Quail Meat in Semi-Finished Food Production - Dashtoyan, A. L.; Gharibyan, K. H.; Sargsyan, H. S.; Baghdasaryan, A. A. (ՀԱԱՀ հիմնադրամ)
Semi-finished food production from the meat raw material has gained a broad application in the consumer market due to ease of its production organization, digestibility, fast consumption, long shelf life and safety. The research considers the development trends in cutlet (semi-finished meat product) manufacturing technologies via quail meat and plant-based filler application. The study aims to improve cutlet production technology through replacing the chicken meat with quail meat and supplementing buckwheat flour. A new cutlet production technology and recipe has been developed and their relevance has been proved.
Keywords: Food Science and Technology